Jazz, gender, historiography: A case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
Cette dissertation se penche sur les interactions entre le jazz, l'identité, la nation et la modernité durant le soi-disant âge d'or du jazz à Montréal (1925-1955). À la croisée de la musicologie, des études de la condition féminine (études féministes noires et méthodes de recherche féministes en particulier), des études des médias et des études culturelles, je propose une réécriture critique de l'histoire du jazz montréalais, attentive au rôle que les femmes racisées et ethnicisées ont joué dans le développement de la scène jazz, et plus largement dans la formation des identités, des plaisirs, et des sons de la modernité québécoise. Le statut particulier de Montréal comme ville-spectacle en fait un riche laboratoire pour étudier les relations de collaboration créative entre les artistes (musiciens.ennes, chanteurs.euses, danseurs.euses) actifs sur le circuit du spectacle de variété noir du début du XXe siècle. Cette recherche met également en lumière la relation discursive qu'entretiennent le jazz et le vice dans l'entre-deux-guerres québécois, en particulier quant à l'incarnation sexuée et racisée de la moralité. Finalement, cette dissertation présente la première écoute critique ainsi que les premières notes biographiques détaillées d'artistes féminines de jazz montréalaises telles que les pianistes Vera Guilaroff et Ilene Bourne, des ensembles féminins comme les Sœurs Spencer et le Montreal Melody Girls Orchestra, des danseuses et chanteuses de variété noires telles que Tina Baines Brereton, Bernice Jordan Whims, Mary Brown, Natalie Ramirez, et Marie-Claire Germain, ainsi que l'enseignante de piano Daisy Peterson Sweeney et les enseignantes de danse Ethel Bruneau et Olga Spencer Foderingham.
Keywords: 1900-1999; 1920-1929; 1930-1939; 1940-1949; 1950-1959; DIG; amérique du nord; amériques; approches et analyses; arts; canada; discipline; femmes* artistes; histoire; histoire et politique; historiographie; intersectionnalité; montréal; musique; mémoires/thèses; point de vue situé; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Aux marges de l'emploi: parcours de travailleuses domestiques québécoises, 1950-2000 - Charron, Catherine (Les éditions du remue-ménage, 2018)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; travail; travail domestique

“I can never be too comfortable”: Race, gender, and emotion at the Hospital Bedside - Cottingham, Marci D.; Johnson, Austin H.; Erickson, Rebecca J. (Qualitative Health Research, 2018)
In this article, we examine how race and gender shape nurses’ emotion practice. Based on audio diaries collected from 48 nurses within two Midwestern hospital systems in the United States, we illustrate the disproportionate emotional labor that emerges among women nurses of color in the white institutional space of American health care. In this environment, women of color experience an emotional double shift as a result of negotiating patient, coworker, and supervisor interactions. In confronting racist encounters, nurses of color in our sample experience additional job-related stress, must perform disproportionate amounts of emotional labor, and experience depleted emotional resources that negatively influence patient care. Methodologically, the study extends prior research by using audio diaries collected from a racially diverse sample to capture emotion as a situationally emergent and complex feature of nursing practice. We also extend research on nursing by tracing both the sources and consequences of unequal emotion practices for nurse well-being and patient care.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; infirmières; intersectionnalité; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; sexisme; systèmes d'oppressions; systèmes hospitaliers; thématiques; travail; travail émotionnel; états-unis

Dancing backwards in high heels: Female professors experience more work demands and special favor requests, particularly from academically entitled students - El-Alayli, Amani; Hansen-Brown, Ashley A.; Ceynar, Michelle (Sex Roles, 2018)
Although the number of U.S. female professors has risen steadily in recent years, female professors are still subject to different student expectations and treatment. Students continue to perceive and expect female professors to be more nurturing than male professors are. We examined whether students may consequently request more special favors from female professors. In a survey of professors (n = 88) across the United States, Study 1 found that female (versus male) professors reported getting more requests for standard work demands, special favors, and friendship behaviors, with the latter two mediating the professor gender effect on professors’ self-reported emotional labor. Study 2 utilized an experimental design using a fictitious female or male professor, with college student participants (n = 121) responding to a scenario in which a special favor request might be made of the professor. The results indicated that academically entitled students (i.e., those who feel deserving of success in college regardless of effort/performance) had stronger expectations that a female (versus male) professor would grant their special favor requests. Those expectations consequently increased students’ likelihood of making the requests and of exhibiting negative emotional and behavioral reactions to having those requests denied. This work highlights the extra burdens felt by female professors. We discuss possible moderators of these effects as well as the importance of developing strategies for preventing them. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: amériques; approches et analyses; discipline; femmes professeures; milieux universitaires; projet charge mentale; psychologie; psychologie sociale; rapports sociaux de sexe; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; travail émotionnel; états-unis

Les solidarités familiales sous l’angle du travail: un siècle au Québec - Kempeneers, Marianne; Van Pevenage, Isabelle; Dandurand, Renée B. (Nouvelles Questions Féministes, 2018)
Les femmes sont le pivot des solidarités familiales, c’est un fait solidement documenté. Malgré cette évidence empirique, les solidarités familiales n’occupent qu’une place fort discrète dans l’univers théorique des rapports sociaux de sexe, contrairement par exemple au travail domestique ou, plus récemment, au travail du care. Les auteures s’interrogent ici sur cet état de fait. Elles proposent ensuite une lecture des solidarités familiales avec, pour ancrage, le paradigme fondateur que constitua la refonte du concept de travail par les courants féministes matérialistes. Adoptant une perspective historique et macrosociologique, cet article est l’occasion de prendre du recul face à un certain nombre de résultats issus d’une vaste enquête que les auteures avaient menée en 2004 sur les transformations des solidarités familiales au Québec au long du XXe siècle. La profondeur historique de cette enquête fait en sorte que ces données, bien que recueillies en 2004, restent pertinentes pour leur propos, à savoir jeter un éclairage sur les logiques reliant les évolutions concomitantes des solidarités familiales, du travail des femmes et des politiques publiques au Québec durant ce siècle crucial de son histoire.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; famille; histoire et politique; hétérosexualité; inégalités; maternité; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Emploi du temps : la charge de travail totale, le travail non rémunéré et les loisirs - Moyser, Melissa; Burlock, Amanda (Statistiques Canada, 2018)
Keywords: amériques; approches et analyses; canada; inégalités; projet charge mentale; régions géographiques; statistiques; systèmes d'oppressions; thématiques; travail; travail domestique; travail invisible

My butch career: A memoir - Newton, Esther (Duke University Press, 2018)
During her difficult childhood, Esther Newton recalls that she “became an anti-girl, a girl refusenik, caught between genders,” and that her “child body was a strong and capable instrument stuffed into the word ‘girl.’” Later, in early adulthood, as she was on her way to becoming a trailblazing figure in gay and lesbian studies, she “had already chosen higher education over the strongest passion in my life, my love for women, because the two seemed incompatible.” In My Butch Career Newton tells the compelling, disarming, and at times sexy story of her struggle to write, teach, and find love, all while coming to terms with her identity during a particularly intense time of homophobic persecution in the twentieth century. Newton recounts a series of traumas and conflicts, from being molested as a child to her failed attempts to live a “normal,” straight life in high school and college. She discusses being denied tenure at Queens College—despite having written the foundational Mother Camp—and nearly again so at SUNY Purchase. With humor and grace, she describes the influence her father Saul's strong masculinity had on her, her introduction to middle-class gay life, and her love affairs—including one with a well-known abstract painter and another with a French academic she met on a spur-of-the-moment trip to Mexico and with whom she traveled throughout France and Switzerland. By age forty, where Newton's narrative ends, she began to achieve personal and scholarly stability in the company of the first politicized generation of out lesbian and gay scholars with whom she helped create gender and sexuality studies. Affecting and immediate, My Butch Career is a story of a gender outlaw in the making, an invaluable account of a beloved and influential figure in LGBT history, and a powerful reminder of just how recently it has been possible to be an openly queer academic.
Keywords: amériques; approches et analyses; autobiographie; butch; histoire et politique; hétérosexisme; identités LGBTQIA2+; queer; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; violences; états-unis

Travail invisible : portraits d'une lutte féministe inachevée - Robert, Camille; Toupin, Louise (Remue-ménage, 2018)
Encore invisible, le travail des femmes? La question peut faire sourciller tant les féministes ont obtenu des gains sur ce front au cours des dernières décennies. Or, si les femmes ont massivement intégré le marché de l'emploi, le travail dit invisible, majoritairement effectué par celles-ci, n'a fait que croître et se complexifier. En plus du strict travail ménager, il se présente sous de multiples visages: la charge mentale de l'organisation familiale, le travail invisible d'intégration des femmes immigrantes, le travail des proches aidantes, celui des aides familiales venues d'ailleurs, des femmes autochtones et racisées, des étudiantes stagiaires, ou encore, des travailleuses du sexe. Comment se décline l'enjeu du travail invisible dans différents milieux, et où en sont les revendications pour faire reconnaître ce travail et le sortir de l'ombre? Rassemblant des militantes féministes et des intellectuelles engagées sur ces questions, cet ouvrage collectif entend remettre le sujet du travail invisible à l'ordre du jour politique tout en proposant des pistes de réflexion et de mobilisation concrètes
Keywords: amériques; approches et analyses; canada; care; cours; fem1300; femmes* autochtones; femmes* immigrantes; inégalités; premier cycle; québec; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; travail du care; travail du sexe

Des luttes intimes, des luttes collectives - Seery, Annabelle (Travail invisible. Portrait d’une lutte féministe inachevée, 2018)
Keywords: 2000 à aujourd'hui; amériques; charge mentale; couple hétérosexuel; famille; inégalités hommes-femmes; maternité; militance; projet charge mentale; périodes historiques; québec; régions géographiques; thématiques; travail

Byproductive labor: A feminist theory of affective labor beyond the productive-reproductive distinction - Whitney, Shiloh (Philosophy and Social Criticism, 2018)
My aim in this paper is to introduce a theory of affective labor as byproductive, a concept I develop through analysis of the phenomenology of various affective labor practices in dialog with feminist scholarship, both on gendered and racialized labor, and on affect and emotion. I motivate my theory in the context of literature on affective and emotional labor in philosophy and the social sciences, engaging the post-Marxist literature on affective and immaterial labor and emphasizing feminist critiques. I argue that affective labor is not only the work of producing affects for others to consume or the reproductive work that rejuvenates and sustains labor power and social life, but also the work of metabolizing waste affects and affective byproducts. Thus, byproductive labor is a neologism I develop to bring into view an affective economy and indeed a political economy of affects to the side of the distinction between productive and reproductive labor in its paid and unpaid variants. I make three central claims: (1) affective labor invariably creates byproducts in the embodied subjectivity of the worker; (2) the unique kind of affective expenditure I call “byproductive” (metabolizing affective surplus, containing affective waste, and producing depleted affective agency) is a defining feature of affective labor not circumscribed by the productive-reproductive distinction; and (3) the marginalized forms of subjectivity and depleted agency constituted through the intersections of this labor with hierarchies of gender, race, and migrant status or global class are themselves byproducts of affective labor. Thus, theorizing affective labor as byproductive captures the uniqueness of affective labor and the forms of exploitation unique to it, but also explains the interaction of affective labor with forms of power that operate through subjection and marginalization. © The Author(s) 2018.
Keywords: amériques; discipline; histoire et politique; philosophie; projet charge mentale; régions géographiques; sciences humaines; thématiques; travail; travail affectif; travail émotionnel; états-unis

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Prendre en compte les femmes à bas salaires et racisées - Yerochewski, Carole (Nouveaux Cahiers du socialisme, 2018)
Keywords: amériques; approches et analyses; care; cours; discipline; fem1300; inégalités; mouvement syndical; mouvements des femmes*; premier cycle; québec; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail